تصميم المنهج المبني على المواقف في مركز اللغة العربية بمعهد دار العلوم بانيوأنيار باميكاسان - Nurul Hadi (OKARA: Jurnal Bahasa dan Sastra, 2015)
In this research, the researcher used research & development (R&D) methodology with quantitative approach. There are four procedures in this research; namely (1) analyzing the situation of the usage of Arabic language needed by students, (2) developing a situational based syllabus for Arabic language teaching at the Arabic language center, (3) validating the product of syllabus that has been designed, (4) revising the product of syllabus having been designed that is appropriately used in Arabic language center. The result of this research is producing a situational based syllabus for Arabic language at the Arabic language center of Pesantren Darul Ulum Banyuanyar Pamekasan Madura which has been validated by three experts in the field of Arabic language teaching curriculum. After that, the syllabus product is presented before the director and all teachers to get their approval that this curriculum design is able to be appropriately used at Arabic language center. To approve this syllabus design, they answered questions on the questionnaire given by the researcher, that 90-100% of each point of the questionnaire related to the appropriateness of the syllabus was answered. As the result, developing a situational based syllabus for Arabic language teaching having been designed by the researcher is appropriate to be implemented in Arabic language center of Pesantren Darul Ulum Banyuanyar Pamekasan Madura.